High Oncolytic Activity of a Double-Deleted Vaccinia Virus Copenhagen Strain against Malignant Pleural Mesothelioma - Delaunay, Tiphaine (Mol Ther Oncolytics, 2020)
Malignant pleural mesothelioma (MPM) is a cancer of the pleura that lacks efficient treatment. Oncolytic immunotherapy using oncolytic vaccinia virus (VV) may represent an alternative therapeutic approach for the treatment of this malignancy. Here, we studied the oncolytic activity of VV thymidine kinase (TK)-ribonucleotide reductase (RR)-/green fluorescent protein (GFP) against MPM. This virus is a VV from the Copenhagen strain that is deleted of two genes encoding the TK (J2R) and the RR (I4L) and that express the GFP. First, we show in vitro that VVTK-RR-/GFP efficiently infects and kills the twenty-two human MPM cell lines used in this study. We also show that the virus replicates in all eight tested MPM cell lines, however, with approximately a 10-fold difference in the amplification level from one cell line to another. Then, we studied the therapeutic efficiency of VVTK-RR-/GFP in non-obese diabetic (NOD) severe combined immunodeficient (SCID) mice that bear peritoneal human MPM tumors. One intraperitoneal infection of VVTK-RR-/GFP reduces the tumor burden and significantly increases mice survival compared to untreated animals. Thus, VVTK-RR- may be a promising oncolytic virus (OV) for the oncolytic immunotherapy of MPM.